The Interplay between Estrogen and Fetal Adrenal Cortex - Jovana Kaludjerovic; Wendy E. Ward (Journal of Nutrition and Metabolism)
Estrogen is a steroid hormone that regulates embryogenesis, cell proliferation and differentiation, organogenesis, the timing of parturition, and fetal imprinting by carrying chemical messages from glands to cells within tissues or organs in the body. During development, placenta is the primary source of estrogen production but estrogen can only be produced if the fetus or the mother supplies dehydroepiandrosterone (DHEA), the estrogen prohormone. Studies show that the fetal zone of the fetal adrenal cortex supplies 60% of DHEA for placental estrogen production, and that placental estrogen in turn modulates the morphological and functional development of the fetal adrenal cortex. As such, in developed countries where humans are exposed daily to environmental estrogens, there is concern that the development of fetal adrenal cortex, and in turn, placental estrogen production may be disrupted. This paper discusses fetal adrenal gland development, how endogenous estrogen regulates the structure and function of the fetal adrenal cortex, and highlights the potential role that early life exposure to environmental estrogens may have on the development and endocrinology of the fetal adrenal cortex.